Revisiting the Malaise of the Ummah: A way forward - Ariffin, Adlina (American Scientific Publishers, 2017)
This paper attempts to discuss the malaise of the Muslim ummah by presenting the essential factors that impede its development in the contemporary world according to the framework propounded by Faruqi (1989) which are the decline of intellect and methodology. It brings forth and discusses the ideas propounded by renowned Muslim scholars such as Abdul Hamid Abu Sulayman, Mohd Kamal Hassan, Ismail al-Faruqi, Al-Attas etc. and relate them to the core issues faced by Muslims worldwide. It also aims to provide some suggestions for Muslims to tackle these issues constructively.